Are zombie firms really contagious? - Norbert Ernst; Michael Sigmund (Oesterreichische Nationalbank (OeNB), 2023)
We test the hypotheses that zombie firms are less productive and have lower employment growth and lower gross investment ratios than non-zombie firms in the same industry sector and that they are a source of contagion for the latter. Ever since Caballero et al. (2008), it has been taken for granted that zombie firms cause contagion in non-zombie firms that ultimately leads to a misallocation of resources. Based on a yearly sample of around 8,000 firms that are observed between 2008 and 2018, we estimate the total factor productivity with the most common methods for the Cobb-Douglas and the translog production function that go beyond the Solow residual approach with fixed elasticities. We use four zombie firm definitions based on subsidized loans and the interest coverage ratio. As expected, we find that non-zombie firms are more productive, have a higher log employment growth and a higher gross investment ratio. However, we do not find any economically significant zombie firm contagion effects in non-zombie firms.
Keywords: D24; E22; C23; 330; production function; total factor productivity; zombie firms